Improving private land conservation with outcome‐based biodiversity payments. Issue 3 (21st February 2018) - McDonald, Jane A.; Helmstedt, Kate J.; Bode, Michael; Coutts, Shaun; McDonald‐Madden, Eve; Possingham, Hugh P.
Abstract: Payments to private landholders for providing biodiversity land can improve conservation outside protected areas. Input‐based payments are widely used despite evidence they are often ineffective at improving biodiversity outcomes. Meanwhile, little has been done to assess how to use outcome‐based payments to maximize biodiversity, despite growing academic interest. We compare different outcome‐based allocation methods to assess which returns the greatest benefits for biodiversity. We predicted the likely landholder actions in response to outcome‐based payments. We incorporated strategic interactions between landholders under four different funding allocation methods: the commonly applied "set‐price" allocation method; capacity‐based payments; proportional payment; and payment for change. We compared biodiversity outcomes (percentage change in abundance of a species of conservation interest), return on investment and cost‐effectiveness of each method. The set‐price allocation method, despite its common usage, is the least cost‐effective method that we test. Regardless of cost, it only results in better biodiversity outcomes than other methods under a very narrow range of conditions (high initial target species abundance and low profitability). The profitability of the property, and to a lesser degree initial population size, will influence which allocation method will perform best. Most perform well when the initial population of the species of conservation interest is very small and profitability negligible. Only one method—based on change in population—performs well across all scenarios. This method outperforms the others particularly when the property has a higher profitability and low initial numbers of animals. Policy implications . Pursuing conservation on private land using outcome‐based payments for biodiversity can result in varied levels of success depending on the allocation methods used to support payment decisions. Allocation method choice should be based on a transparent analysis that incorporates both the dynamics of the ecological system and interactions between individual landholders. This analysis can guide adoption of funding allocation methods that greatly increase biodiversity outcomes.